Biosynthesis of the Iron-Molybdenum Cofactor of Nitrogenase - Hu, Yilin (American Society for Biochemistry and Molecular Biology, 2013)
The iron-molybdenum cofactor (the M-cluster) serves as the active site of molybdenum nitrogenase. Arguably one of the most complex metal cofactors in biological systems, the M-cluster is assembled through the formation of an 8Fe core prior to the insertion of molybdenum and homocitrate into this core. Here, we review the recent progress in the research area of M-cluster assembly, with an emphasis on our work that provides useful insights into the mechanistic details of this process.